Resistance evolution under potentiated sulphonamide pressure in Escherichia coli - Kerek, Ádám; Török, Bence; Szabó, Ábel; Laczkó, Levente; Kardos, Gábor; Bányai, Krisztián; Kaszab, Eszter; Bali, Krisztina; Jerzsele, Ákos (Frontiers in Veterinary Science, 2025)
IntroductionAntimicrobial resistance (AMR) poses an escalating global health threat. Potentiated sulphonamides are widely used in both veterinary and human medicine. This study aimed to investigate the in vitro adaptation of Escherichia coli strains to increasing concentrations of potentiated sulphonamides, focusing on co-selection and the genetic mechanisms of resistance.MethodsThe MEGA-plate evolutionary model was used to expose E. coli ATCC 25922 to increased concentrations (0 × to 1000×) of a potentiated sulphonamide. Clones isolated from different concentration zones were analyzed for phenotypic resistance via minimum inhibitory concentration (MIC) testing and genotypically through next-generation sequencing.ResultsIn strains adapted to 1000 × potentiated sulphonamide, MIC values significantly increased for most tested antibiotics. Mutations were identified in key folate pathway genes (folP, folA), as well as in efflux pump regulator genes (emrR, marR, acrR, mdtM). These genetic changes indicated activation of multiple multidrug efflux systems, including acrAB-tolC, emrAB-tolC, and mdtEF-tolC. Mutations were also detected in genes associated with SOS response regulation (recN, recQ, uvrB), suggesting stress-induced genetic adaptation. In vitro microevolutionary adaptation to potentiated sulphonamide exposure induced broad genetic changes in E. coli, potentially driving cross-resistance through co-selection. The MEGA-plate method proved to be a robust tool for tracking resistance development and dissecting complex resistance mechanisms.DiscussionThese findings underscore the need for cautious use of combination antimicrobials, as they may elicit pleiotropic resistance responses beyond their intended targets.